RELEVANCE OF ACCOUNTING INFORMATION TOWARDS SHARE PRICES OF JAKARTA ISLAMIC INDEX (JII) LISTED COMPANIES - Fitri Utami; Slamet Haryono; Abdurrahman Niarman (Imara: JURNAL RISET EKONOMI ISLAM, 2021)
Accounting information has an important role in describing the condition and performance of a company. However, some investors have not fully used accounting information in sorting out share purchases. This study examines the relevance of accounting information to share prices in companies listed on the Jakarta Islamic Index (JII) for the period 2015 to 2020. The accounting information used is Earnings per Share (EPS), Book Value (BV), Return On Equity (ROE), Net Profit Margin (NPM), and Current Ratio (CR). With the panel data regression analysis method, the researcher found that collectively all accounting information (EPS, BV, ROE, NPM and CR) were stated to have relevance value in explaining their effect on stock prices. Individually, only BV and ROE have relevance value in influencing stock prices. As for EPS, NPM and CR have no value relevance to the share price of companies listed on the Jakarta Islamic Index (JII) for the period 2015 to 2019